Stability Analysis of DC-link Voltage Control on Autonomous Micro Hydro Power Plant System - Feri Yusivar; M. Shanizal; A. Subiantoro; R. Gunawan (Institute of Advanced Engineering and Science, 2014)
Micro Hydro Power Plant has become one of the interesting topics to be researched nowadays. This paper deals with the stability analysis on control system of excitation voltage in Micro Hydro Power Plant. The control of this voltage can be achieved by controlling the Permanent Magnet Synchronous Machine (PMSM) with particular algorithm so the voltage on the DC-link part of the system can be controlled. Without knowing the exact specification of system parameters, the system will be most likely unstable. The DC-link control system is modeled, simulated, and mathematically analyzed so the parameter specification for the stable system can be obtained.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6436